Global profiling of protein–DNA and protein–nucleosome binding affinities using quantitative mass spectrometry - Matthew M. Makowski (Nature Portfolio, 2018)
Quantitative mass spectrometry enables the proteome-wide assessment of biomolecular binding affinities. While previous approaches mainly focused on protein–small molecule interactions, the authors here present a method to probe protein–DNA and protein–nucleosome binding affinities at proteome scale.